2011
DOI: 10.1111/j.1365-2842.2011.02269.x
|View full text |Cite
|
Sign up to set email alerts
|

Social support in chronic pain: development and preliminary psychometric assessment of a new instrument

Abstract: Satisfaction with social support (pain-relevant social support) may influence pain experience and behaviour in patients with chronic pain. Prior studies on measurement of social support, however, have been limited by the use of general, rather than of pain-specific assessment instruments. In this study, a new pain-relevant social support instrument, the Social support and Pain Questionnaire (SPQ), is presented together with an evaluation of its psychometric properties. A literature search was performed to esta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 34 publications
3
16
0
Order By: Relevance
“…This was consistent with other previous studies [15, 26]. In order to get a semantically and conceptually similar version to the original SPQ, the process of translation and cross-cultural adaptation of the original SPQ was carried out.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…This was consistent with other previous studies [15, 26]. In order to get a semantically and conceptually similar version to the original SPQ, the process of translation and cross-cultural adaptation of the original SPQ was carried out.…”
Section: Discussionsupporting
confidence: 81%
“…And when each item was deleted, the values of Cronbach’s alpha remained stable. The value of ICC (0.784, 90% CI: 0.648–0.893) was higher than the values in the original study, indicating good test-retest reliability [15]. For the selection of the time interval, previous study suggested that a period of 2 days to 2 weeks was thought to be suitable [27].…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations